Genomics of Staphylococcus aureus Strains Isolated from Infectious and Non-Infectious Ocular Conditions - Madeeha Afzal; Ajay Kumar Vijay; Fiona Stapleton; Mark D. P. Willcox (MDPI AG, 2022)
Staphylococcus aureus is a major cause of ocular infectious (corneal infection or microbial keratitis (MK) and conjunctivitis) and non-infectious corneal infiltrative events (niCIE). Despite the significant morbidity associated with these conditions, there is very little data about specific virulence factors associated with the pathogenicity of ocular isolates. A set of 25 S. aureus infectious and niCIEs strains isolated from USA and Australia were selected for whole genome sequencing. Sequence types and clonal complexes of S. aureus strains were identified by using multi-locus sequence type (MLST). The presence or absence of 128 virulence genes was determined by using the virulence finder database (VFDB). Differences between infectious (MK + conjunctivitis) and niCIE isolates from USA and Australia for possession of virulence genes were assessed using the chi-square test. The most common sequence types found among ocular isolates were ST5, ST8 while the clonal complexes were CC30 and CC1. Virulence genes involved in adhesion (ebh, clfA, clfB, cna, sdrD, sdrE), immune evasion (chp, esaD, esaE, esxB, esxC, esxD), and serine protease enzymes (splA, splD, splE, splF) were more commonly observed in infectious strains (MK + conjunctivitis) than niCIE strains (p = 0.004). Toxin genes were present in half of infectious (49%, 25/51) and niCIE (51%, 26/51) strains. USA infectious isolates were significantly more likely to possess splC, yent1, set9, set11, set36, set38, set40, lukF-PV, and lukS-PV (p < 0.05) than Australian infectious isolates. MK USA strains were more likely to possesses yent1, set9, set11 than USA conjunctivitis strains (p = 0.04). Conversely USA conjunctivitis strains were more likely to possess set36 set38, set40, lukF-PV, lukS-PV (p = 0.03) than MK USA strains. The ocular strain set was then compared to 10 fully sequenced non-ocular S. aureus strains to identify differences between ocular and non-ocular isolates. Ocular isolates were significantly more likely to possess cna (p = 0.03), icaR (p = 0.01), sea (p = 0.001), set16 (p = 0.01), and set19 (p = 0.03). In contrast non-ocular isolates were more likely to possess icaD (p = 0.007), lukF-PV, lukS-PV (p = 0.01), selq (p = 0.01), set30 (p = 0.01), set32 (p = 0.02), and set36 (p = 0.02). The clones ST5, ST8, CC30, and CC1 among ocular isolates generally reflect circulating non-ocular pathogenic S. aureus strains. The higher rates of genes in infectious and ocular isolates suggest a potential role of these virulence factors in ocular diseases.